2020
DOI: 10.1038/s41416-020-1022-4
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 favours tumour metastasis via the activation of β-catenin signalling in hepatocellular carcinoma

Abstract: Background High probability of metastasis limited the long-term survival of patients with hepatocellular carcinoma (HCC). Our previous study revealed that Galectin-3 was closely associated with poor prognosis in HCC patients. Methods The effects of Galectin-3 on tumour metastasis were investigated in vitro and in vivo, and the underlying biological and molecular mechanisms involved in this process were evaluated. Results Galectin-3 showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 44 publications
3
46
1
Order By: Relevance
“…LGALS3 plays a signi cant role in the progression and metastasis of colon cancer, acute myeloid leukemia, melanoma, and pituitary tumors [40][41][42][43]. In addition, LGALS3 enhances HCC cell tumorigenesis and metastasis through the β-catenin signaling [44]. A series of studies have demonstrated that Galectin-3 can severe as a biomarker for prognosis predicting of HCC patients which are the same as our results [45][46][47].…”
Section: Discussionsupporting
confidence: 88%
“…LGALS3 plays a signi cant role in the progression and metastasis of colon cancer, acute myeloid leukemia, melanoma, and pituitary tumors [40][41][42][43]. In addition, LGALS3 enhances HCC cell tumorigenesis and metastasis through the β-catenin signaling [44]. A series of studies have demonstrated that Galectin-3 can severe as a biomarker for prognosis predicting of HCC patients which are the same as our results [45][46][47].…”
Section: Discussionsupporting
confidence: 88%
“…LGALS3 plays a significant role in the progression and metastasis of colon cancer, acute myeloid leukemia, melanoma, and pituitary tumors [ 40 43 ]. In addition, LGALS3 enhances HCC cell tumorigenesis and metastasis through the β-catenin signaling [ 44 ]. A series of studies have demonstrated that Galectin-3 can severe as a biomarker for prognosis predicting of HCC patients which are the same as our results [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found that β -catenin expression was decreased in parallel to the attenuation of AKT phosphorylation. In hepatocellular carcinoma, galectin-3 overexpression enhanced metastasis through the PI3K/AKT/GSK-3 β / β -catenin signaling cascade [ 33 ]. Our findings are further supported by a study demonstrating that β -catenin activation was highly dependent on the PI3K/AKT activity but not on the MAPK [ 34 ].…”
Section: Discussionmentioning
confidence: 99%